Therapeutics and biotherapies for COVID 19 - Sterin Prync , Aída E.; Fasciolo, Franco R.; Rosales, Agustina; Vázquez, Nayla S.; Carlucci, Adriana M. (Revista del Hospital Italiano de Buenos Aires, 2022)
Introduction: A new coronavirus outbreak emerged in 2019 in Wuhan, China, causing a shock to the healthcare system around the world; the International Committee on Taxonomy of Viruses named it SARS-CoV- 2, the infectious agent of the COVID-19 disease.The spectrum of severity of the disease is very wide, most patients are not serious, but others can develop pneumonia, with acute respiratory failure being the most frequent cause of mortality.Objective: to analyze and develop the different therapeutic alternatives provided by Biotechnology dedicated to Health, to treat the symptoms of those COVID-19 patients who require it, and thus reduce mortality.Methodology: a review of the available literature from January 2020 in PubMed of the treatments that are still in clinical trials and those that have been approved under emergency use for the disease COVID-19 was performed. Searches were also carried out through Google and Google Scholar for publications of Health organizations in reference to health policies established for therapeutics during the mentioned pandemic.Results: this work addresses the new therapeutic alternatives derived from Biotechnology, which are both in use and in stages of clinical trials, to treat patients who developed COVID-19 included within the segment of biopharmaceuticals and biotherapies. A brief summary of the regulatory status of health entities, the mechanism of action of said therapies and general characteristics of each one is included. Innovative biotherapies that began to be implemented to face the pandemic are included.Conclusions: The coronavirus pandemic has driven the international health system to the test, to provide solutions both from the diagnosis, prevention and treatment of the population to reduce the mortality of patients. This obviously also included the area of Biotechnology applied to health, which has contributed in the three aspects mentioned. The present work focuses on the therapeutic responses that it has provided and that are commercialized or in clinical phases.
Keywords: COVID-19; SARS-CoV-2; biopharmaceuticals; biotherapies; microbiota; ACE 2; monoclonal antibody